People are Creating Policy up There, they are not Coming Down': Nurses' Views on The Expansion of Routine Provider-Initiated HIV Testing and Counselling in Nairobi, Kenya. - Ndirangu, Wambui Eunice; Evans, Catrin (eCommons, 2009)
In this report, we present selected findings from an exploratory piece of qualitative research on HIV testing that was undertaken in 2007-2008 with nurses in Nairobi, Kenya. At the same time, we share our own story of how this research came about and how NHIVNA research funding was able to lay the foundations for a larger study that will hopefully give voice to patients and HIV nurses in Nairobi and will develop HIV nursing research capacity in the country.
Journal Article
Keywords: Nurses' Views; Expansion of Routine Provider-Initiated HIV Testing and Counselling